Rab12 Promotes Radioresistance of HPV-Positive Cervical Cancer Cells by Increasing G2/M Arrest - Huang, Yujie; Tian, Yonghao; Zhang, Wenhao; Liu, Ruijuan; Zhang, Weifang (Frontiers in Oncology, 2021)
Background: HPV-positive (HPV+) cervical cancer cells are more radioresistant compared with HPV-negative (HPV-) cervical cancer cells, but the underlying mechanism is not fully illuminated. Our previous mass spectrometry data showed that Ras-associated binding protein Rab12 was up-regulated by HPV, and this study is to investigate the role of Rab12 in the radioresistance of HPV-positive cervical cancer cells. Methods: CCK-8 assay, colony formation assay, flow cytometry and Western blot were performed to determine cell proliferation, apoptosis, cell cycle distribution and protein expressions. DNA damage and repair levels were measured by comet assays and detection of γ-H2AX, XRCC4 and pBRCA1 protein expressions. Results: Rab12 mRNA and protein expressions were up-regulated in cervical cancer tissues and HPV+ cervical cancer cells. Knockdown of Rab12 enhanced radiosensitivity while overexpression of Rab12 promotes radioresistance. Knockdown of Rab12 alleviated G2/M arrest by decreasing p-Cdc2(Tyr15) after radiation, which was a result of the reduction of p-Cdc25C(Ser216). Rab12 knockdown caused more DNA double-strand breaks (DSBs) and inhibited DNA homologous recombination repair (HRR) after radiation. Instead, overexpression of Rab12 enhanced radioresistance by increasing G2/M arrest, which provided more time for DNA HRR. Conclusions: Rab12 may serve as a potential therapeutic target to improve clinical treatment outcome of cervical cancer.